Prototype of an enabling table and automatic glass cutter - Velásquez Costa, José Antonio (2016)
This paper describes the implementation of a prototype automated glass cutting, in order to increase the level of product quality and productivity in a glass company. The prototype was developed with actuators and sensors, which are connected to a programmable logic controller (PLC), so it can control the process automatically, while also reducing bottlenecks and the percentage of wastage in the cutting process glass. This project was undertaken by the students Itala Condezo Collado and Susana Lachira Alvines in the course Manufacturing Processes II Computer-assisted from the Program Industrial Engineering at Universidad Ricardo Palma.